PROPAGANDA AND THE DANGER OF EXTREMIST CURRENTS - RECURRING THEMES AND MANIFESTATIONS IN THE MODERN AND RECENT HISTORY OF ROMANIA AND EUROPE - Viorel BUȚA; Răzvan Nicolae MANOLIU (Annals: Series on Military Sciences)
Romania, like many other countries, has been exposed to the influence of extremist propaganda in various forms throughout its recent history. From the totalitarian regimes of the 20th century to contemporary movements of political and social extremism, propaganda has played an essential role in shaping public opinions and mobilizing the masses. This article explores the evolution of extremist propaganda in Romania, from the interwar period to the present, analyzing its mechanisms, its impact on society, and ways to combat this phenomenon.